Factors Affecting Return on Assets in 5 Conventional Commercial Banks in 2015-2022 - Ratnasari, Desy; Nirmala, Tiara (Lafadz Jaya Publisher, 2024)
This study aims to analyze the factors that affect Return on Assets in 5 conventional commercial banks in 2015-2022. The research method used is panel data with Microsoft Excel and E-Views 10 as analysis tools. Factors that affect Return on Assets in this study include economic factors, environmental factors, and internal bank factors. Economic factors consist of BI Rate and Inflation. Environmental factors are Green Banking which is proxied with the Green Banking Disclosure Index and internal bank factors, namely BOPO. The results of the test found that the variables Inflation, Green Banking proxied Green Banking Disclosure Index, and BOPO have a significant negative effect on Return on Assets, while the BI Rate has a significant positive effect on Return On Assets in 5 conventional commercial banks.